Feasibility and acceptability of magnetic resonance imaging and electroencephalography for child neurodevelopmental research in rural Ethiopia - Workneh, Firehiwot; Chin, Theresa I.; Yibeltal, Kalkidan; North, Krysten; Fasil, Nebiyou; Tarekegn, Workagegnhu; Abate, Betelhem Haimanot; Mulugeta, Sarem; Asmamaw, Gellila; Teklehaimanot, Atsede; Troller-Renfree, Sonya V.; Jensen, Sarah K. G.; et al. (Frontiers in Public Health, 2025)
BackgroundMagnetic resonance imaging (MRI) and electroencephalography (EEG) are valuable tools for studying neuroanatomical and electrophysiological features of early brain development. Studies implementing neuroimaging tools in low- and middle-income countries are still rare, and there is limited data on the acceptability of such tools among rural communities. The present study explores the perceptions, feasibility, and acceptability of introducing MRI and EEG for child development research in the rural Amhara region of Ethiopia.MethodsA total of 40 in-depth interviews were conducted among community members (n = 24) and clinicians (n = 16). A semi-structured interview included four themes: (1) Baseline imaging knowledge, (2) Perceptions of MRI and EEG, (3) Facilitators and barriers to acceptability of MRI and EEG, and (4) Recommendations to improve MRI and EEG uptake. Interviews were conducted in Amharic, the local language. All interviews were transcribed verbatim to Amharic, translated into English, and double-coded. We used thematic analysis to organize data according to predefined and emerging themes.ResultsKnowledge of MRI and EEG was limited, and none of the community members had previous experiences with either technology. Broadly, participants responded positively to our introductory videos showing MRI and EEG acquisition and expressed high levels of acceptability. However, participants reported concerns about possible harms related to radiation, electrical shock, and injury from MRI/EEG procedures. Those with lesser education were identified to be less accepting of MRI/EEG. In addition, several mothers expressed that consent from their husbands was necessary for their child’s participation in neurodevelopmental research. Potential logistical barriers identified included transportation challenges to the neuroimaging study sites, especially for rural-dwelling families. Creating awareness, using explanatory videos, and engaging community members and clinicians were recommended to facilitate acceptance of EEG and MRI.ConclusionIn this formative study, MRI and EEG were viewed as acceptable methods for assessing child neurodevelopment in rural areas of Ethiopia. Community members’ and clinicians’ views were impacted largely by social, religious, educational, and logistical aspects. Concerns related to MRI radiation, electrical shock, and injuries from EEG can be addressed through awareness creation and education. Engaging community leaders and healthcare providers is key to improving acceptability.